Simulation of Photovoltaic Thermoelectric Battery Characteristics - Esman, A. K.; Zykov, G. L.; Potachits, V. A.; Kuleshov, V. K. (БНТУ, 2021)
Solar radiation is an environmentally friendly and affordable energy source with high release of energy. The use of a photovoltaic thermoelectric battery makes it possible to increase the efficiency of converting solar and thermal radiation into electrical energy, both on serene and cloudy days. An original battery structure with photovoltaic and thermoelectric converters is proposed. The 3D model of the proposed photovoltaic thermoelectric battery was realized in the COMSOL Multiphysics software environment with the use of a heat transfer module. The simulation was performed for the geographical coordinates of Minsk and taking into account the diurnal and seasonal variations of both the ambient temperature and the power density of the concentrated AM1.5 solar spectrum, the maximum value of which being varied from 1 to 500 kW/m2. The dependences of the maximum temperature values of the photovoltaic thermoelectric battery and the thermoelectric converters as well as temperature gradient patterns in the thermoelectric converters have been calculated. The dependences of the maximum temperature gradient values inside the thermoelectric converters on the solar power density are obtained. The graphs of the temperature gradients inside the thermoelectric converters of the photovoltaic thermoelectric battery by concentrated solar radiation versus the time of day in the middle of July and January are provided. It is shown that the output voltage increases up to the maximum values of 635 and 780 mV, respectively, in January and in July were achieved due to the temperature stabilization of the back side of the external electrodes of the proposed device.
Моделирование характеристик фототермоэлектрической батареи